CENTESIMAL COMPOSITION OF TYPICAL FRUTIS FROM BRAZILIAN SAVANA : A LITERATURE REVIEW (CIPEEX, 2022)
THE CENTESIMAL COMPOSITION OF A FOOD REFLECTS ITS NUTRITIONAL OR CALORIC VALUE, AS WELL AS THE BIOAVAILABILITY AND PROPORTION OF NUTRIENTS IN 100G OF THE PRODUCT. THE OBJECTIVES OF PROXIMATE COMPOSITION ARE TO RECOGNIZE THE AVAILABILITY OF FOODS AND THEIR PHYSICOCHEMICAL CHARACTERISTICS, AS WELL AS THE COMPOSITION OF NUTRIENTS AND THE IMPORTANCE OF THE VARIETY AND DIVERSITY OF FOODS IN THE DIET OF INDIVIDUALS AND THE COMMUNITY. THE IMPORTANCE OF THE CENTESIMAL COMPOSITION ALSO COVERS THE AREAS OF AGRICULTURE, INDUSTRY AND FOOD MARKETING, SINCE BRAZIL IS A COUNTRY WITH VAST BIODIVERSITY AND LARGE TERRITORIAL EXTENSION. CURRENTLY, THERE IS A SCARCITY OF MATERIAL THAT GATHERS THE NUTRITIONAL INFORMATION OF TYPICAL CERRADO FRUITS. IN THIS SENSE, THIS LITERATURE REVIEW AIMS TO BUILD A FOOD COMPOSITION TABLE OF TYPICAL CERRADO FRUITS. WE ANALYZED 27 ORIGINAL WORKS THAT CONTAINED THE PROXIMATE COMPOSITION OF ONE OR MORE CERRADO FRUITS. THEREFORE, EVEN WITH THE PRODUCTION OF THIS MATERIAL, IT IS NECESSARY THAT MORE STUDIES ARE CARRIED OUT WITH THE PROXIMATE COMPOSITION OF TYPICAL FOODS FROM THE CERRADO AND OTHER REGIONS.
Keywords: Centesimal Composition; Savana; Fruits; Savana Fruits